PELAKSANAAN PEMBELAJARAN JARAK JAUH (PJJ) DI SEKOLAH INKLUSI SD NEGERI 1 TRIRENGGO TAHUN PELAJARAN 2020/2021 - Eva Royani (Jurnal PGSD Indonesia, 2021)
AbstractThis research was conducted at inclusive school of Trirenggo 1 Elementary School. The first objective of this study was to find out the teacher's planning for distance learning in grade V students Trirenggo 1 Elementary School. The second objective of this study was to find out the process of distance learning in grade V students Trirenggo 1 Elementary School. The third objective of this study was to find out the form of distance learning evaluation conducted by teachers in grade V students Trirenggo 1 Elementary School.This study applied qualitative research method. The subjects of this study were two classroom teachers, a shadow teacher and students at Trirenggo 1 Elementary School.The data were collected through; observation, interview and documentation. The data were analyzed using the steps proposed by Miles and Huberman through data reduction, data presentation, and conclusions or verification. The validity of the data is conducted by triangulation.The results of this study indicated that the implementation of distance learning in grade V students Trirenggo 1 Elementary School has been carried out quite well. The students in grade V students Trirenggo 1 Elementary School  consist of 28 regular students and 2 slow learners. The planning of distance learning (online) for slow learners and regular students in  grade V students Trirenggo 1 Elementary School was designed similarly by the classroom teachers. The fifthgrade teachers at  Trirenggo 1 Elementary School used learning videos as a medium that was delivered via WhatsApp. The learning materials for slow learners were designed differently by lowering the level of difficulty of the materials compared to the regular students’ materials. Slow learners tended to be slow in understanding the material, so they felt trouble in following the distance learning pace. Their troubles were task collection, learning readiness, and the material comprehension. The evaluation of distance learning conducted by the fifth-grade teachers of  Trirenggo 1 Elementary School covers the cognitive, affective, and psychomotor domains through WhatsApp.Keywords: Distance learning, Implementation, Inclusive elementary school.